2010
DOI: 10.1089/acm.2009.0560
|View full text |Cite
|
Sign up to set email alerts
|

Effect of T'ai Chi Exercise on Biochemical Profiles and Oxidative Stress Indicators in Obese Patients with Type 2 Diabetes

Abstract: T'ai chi exercise practiced by patients who are obese and have type 2 diabetes is efficient and safe when supervised by professionals and helps improve parameters, such as BMI, lipid profile, C-reactive protein, and malondialdehyde. Periodic monitoring of blood glucose, blood pressure, heart rate, breathing, physical fitness, and symptoms of discomfort of patients who exercise helps prevent injury. Simple, gentle TCE can be applied as regular daily exercise for patients with type 2 diabetes even when such pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
137
2
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(148 citation statements)
references
References 39 publications
4
137
2
5
Order By: Relevance
“…Three trials were excluded for Tai Chi combined with other interventions, no baseline data including lipid profiles were reported in Records excluded on title (n=103): 63 comments, reviews or editorial 1 adolescent and child 7 animal or in-vitro studies 32 not relevant one trial, and it was not possible to extract lipid data from the outcomes in two trials. Six randomized placebo-controlled trials (Tsai et al, 2003;Thomas et al, 2005;Lam et al, 2008;Zhang and Fu, 2008;Chen et al, 2010;Lu and Kuo, 2012) fulfilled the inclusion criteria and were included in the final meta-analysis.…”
Section: Study Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…Three trials were excluded for Tai Chi combined with other interventions, no baseline data including lipid profiles were reported in Records excluded on title (n=103): 63 comments, reviews or editorial 1 adolescent and child 7 animal or in-vitro studies 32 not relevant one trial, and it was not possible to extract lipid data from the outcomes in two trials. Six randomized placebo-controlled trials (Tsai et al, 2003;Thomas et al, 2005;Lam et al, 2008;Zhang and Fu, 2008;Chen et al, 2010;Lu and Kuo, 2012) fulfilled the inclusion criteria and were included in the final meta-analysis.…”
Section: Study Selectionmentioning
confidence: 99%
“…Most of the subjects were elderly Chinese. Subject characteristics included type 2 diabetes (Lam et al, 2008;Zhang and Fu, 2008;Chen et al, 2010) and obesity (Chen et al, 2010). The trial including obese subjects reported a significant reduction of body mass index (BMI) after practicing Tai Chi (Chen et al, 2010).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations